DNA methylation in adults and during development of the self‐fertilizing mangrove rivulus, Kryptolebias marmoratus. Issue 12 (15th May 2018) - Fellous, Alexandre; Labed‐Veydert, Tiphaine; Locrel, Mélodie; Voisin, Anne‐Sophie; Earley, Ryan L.; Silvestre, Frederic
Abstract: In addition to genetic variation, epigenetic mechanisms such as DNA methylation might make important contributions to heritable phenotypic diversity in populations. However, it is often difficult to disentangle the contributions of genetic and epigenetic variation to phenotypic diversity. Here, we investigated global DNA methylation and mRNA expression of the methylation‐associated enzymes during embryonic development and in adult tissues of one natural isogenic lineage of mangrove rivulus fish, Kryptolebias marmoratus . Being the best‐known self‐fertilizing hermaphroditic vertebrate affords the opportunity to work with genetically identical individuals to examine, explicitly, the phenotypic effects of epigenetic variance. Using the LUminometric Methylation Assay (LUMA), we described variable global DNA methylation at CpG sites in adult tissues, which differed significantly between hermaphrodite ovotestes and male testes (79.6% and 87.2%, respectively). After fertilization, an immediate decrease in DNA methylation occurred to 15.8% in gastrula followed by re‐establishment to 70.0% by stage 26 (liver formation). Compared to zebrafish, at the same embryonic stages, this reprogramming event seems later, deeper, and longer. Furthermore, genes putatively encoding DNA methyltransferases (DNMTs), Ten‐Eleven Translocation (TET), and MeCP2 proteins showed specific regulation in adult gonad and brain, and also during early embryogenesis. Their conserved domains and expression profiles suggest that these proteins play important roles during reproduction and development. This study raises questions about mangrove rivulus' peculiar reprogramming period in terms of epigenetic transmission and physiological adaptation of individuals to highly variable environments. In accordance with the general‐purpose genotype model, epigenetic mechanisms might allow for the expression of diverse phenotypes among genetically identical individuals. Such phenotypes might help to overcome environmental challenges, making the mangrove rivulus a valuable vertebrate model for ecological epigenetic studies. The mangrove rivulus, Kryptolebias marmoratus, is the best‐known self‐fertilizing hermaphroditic vertebrate that allows to work with genetically identical individuals to examine, explicitly, the phenotypic effects of epigenetic variance. The reprogramming event is later, more dramatic and longer than in other described vertebrates. High evolutionary conservation and expression patterns of DNMT, TET, and MeCP2 proteins in K. marmoratus suggest biological roles for each member in gametogenesis and development. Abstract : The mangrove rivulus, Kryptolebias marmoratus, is the best‐known self‐fertilizing hermaphroditic vertebrate that allows to work with genetically identical individuals to examine, explicitly, the phenotypic effects of epigenetic variance. The reprogramming event is later, more dramatic and longer than in other described vertebrates. High evolutionary conservation and expression patterns of DNMT, TET, and MeCP2 proteins in K. marmoratus suggest biological roles for each member in gametogenesis and development.